Comparison of the Birmingham Vasculitis Activity Score and the Five‐Factor Score to Assess Survival in Antineutrophil Cytoplasmic Antibody–Associated Vasculitis: A Study of 550 Patients From Spain (REVAS Registry). Issue 7 (12th June 2020) - Solans‐Laqué, Roser; Rodriguez‐Carballeira, Monica; Rios‐Blanco, Juan Jose; Fraile, Guadalupe; Sáez‐Comet, Luis; Martinez‐Zapico, Aleida; Frutos, Begoña; Solanich, Xavier; Fonseca‐Aizpuru, Eva; Pasquau‐Liaño, Francisco; Zamora, Monica; Oristrell, Joaquim; et al.
Abstract : Objective: To compare the accuracy of the Birmingham Vasculitis Activity Score (BVAS), version 3, and the Five Factor Score (FFS), version 1996 and version 2009, to assess survival in antineutrophil cytoplasmic antibody–associated vasculitis (AAV). Methods: A total of 550 patients with AAV (41.1% with granulomatosis with polyangiitis, 37.3% with microscopic polyangiitis, and 21.6% with eosinophilic granulomatosis with polyangiitis), diagnosed between 1990 and 2016, were analyzed. Receiver operating characteristic (ROC) curves and multivariable Cox analysis were used to assess the relationships between the outcome and the different scores. Results: Overall mortality was 33.1%. The mean ± SD BVAS at diagnosis was 17.96 ± 7.82 and was significantly higher in nonsurvivors than in survivors (mean ± SD 20.0 ± 8.14 versus 16.95 ± 7.47, respectively; P < 0.001). The mean ± SD 1996 FFS and 2009 FFS were 0.81 ± 0.94 and 1.47 ± 1.16, respectively, and were significantly higher in nonsurvivors than in survivors (mean ± SD 1996 FFS 1.17 ± 1.07 versus 0.63 ± 0.81 [ P < 0.001] and 2009 FFS 2.13 ± 1.09 versus 1.15 ± 1.05 [ P < 0.001], respectively). Mortality rates increased according to the different 1996 FFS and 2009 FFS categories. In multivariate analysis, BVAS, 1996 FFS, and 2009 FFS were significantly related to death ( P = 0.007, P = 0.020, P < 0.001, respectively), but the stronger predictor was the 2009 FFS (hazard ratio 2.9 [95% confidence interval 2.4–3.6]). When the accuracy of BVAS, 1996 FFS, and 2009 FFS to predict survival was compared in the global cohort, ROC analysis yielded area under the curve values of 0.60, 0.65, and 0.74, respectively, indicating that 2009 FFS had the best performance. Similar results were obtained when comparing these scores in patients diagnosed before and after 2001 and when assessing the 1‐year, 5‐year, and long‐term mortality. Correlation among BVAS and 1996 FFS was modest (r = 0.49; P < 0.001) but higher than between BVAS and the 2009 FFS (r = 0.28; P < 0.001). Conclusion: BVAS and FFS are useful to predict survival in AAV, but the 2009 FFS has the best prognostic accuracy at any point of the disease course.